Pengaruh Penerapan Prinsip-prinsip Good Corporate Governance Pada Kinerja Bank Perkreditan Rakyat di Kota Denpasar - Sawitri, Putu Putri; Ramantha, I Wayan (E-Jurnal Akuntansi; Vol 23 No 2 (2018)DO - 10.24843/EJA.2018.v23.i02.p11, 2018)
ABSTRACT Good corporate governance is not a new thing in the banking world. Therefore it is necessary to understand the principles of good corporate governance in banking. This study aims to determine the effect of applying the principles of good corporate governance on the performance of Rural Banks in Denpasar. Transparency, accountability, responsibility, independence, and fairness and participation are fundamental principles of GCG implementation and BPR based balanced scorecard performance. This study was conducted by collecting data through questionnaires distributed to 29 BPRs located in Denpasar City with each taken three respondents. The result of the research shows that the application of GCG principles that include transparency, accountability, responsibility, independence, fairness and participation have a positive effect on the performance of Rural Bank in Denpasar. Keywords: good corporate governance, balanced scorecard, performance